2018
DOI: 10.15252/embr.201846632
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections and cancer

Abstract: Infections are estimated to contribute to 20% of all human tumours. These are mainly caused by viruses, which explains why a direct bacterial contribution to cancer formation has been largely ignored. While epidemiological data link bacterial infections to particular cancers, tumour formation is generally assumed to be solely caused by the ensuing inflammation responses. Yet, many bacteria directly manipulate their host cell in various phases of their infection cycle. Such manipulations can affect host cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 107 publications
(130 reference statements)
1
131
0
Order By: Relevance
“…upregulates proinflammatory cytokines, chemokines, and cell adhesion molecules in keratinocytic cells, both primary cultures and SCC lines, through activation of the canonical NF‐κB pathway. In keeping with other bacterial pathogens, we confirmed the inflammatory role played by IKK . Using fluorescent microscopy and Western blot analysis, we demonstrated that phosphorylation of IκB is C. t .‐dependent.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…upregulates proinflammatory cytokines, chemokines, and cell adhesion molecules in keratinocytic cells, both primary cultures and SCC lines, through activation of the canonical NF‐κB pathway. In keeping with other bacterial pathogens, we confirmed the inflammatory role played by IKK . Using fluorescent microscopy and Western blot analysis, we demonstrated that phosphorylation of IκB is C. t .‐dependent.…”
Section: Discussionsupporting
confidence: 83%
“…In keeping with other bacterial pathogens, we confirmed the inflammatory role played by IKK. [65][66][67][68][69] Using fluorescent microscopy and Western blot analysis, we demonstrated that phosphorylation of IκB is C. t.-dependent. Furthermore, the inhibition of IKK by the specific inhibitor PS-1145 70 significantly reduced the mRNA and protein expression of proinflammatory molecules induced by C. t., indicating these effects are mediated, at least in major part, by IKK.…”
mentioning
confidence: 95%
“…This further suggests that bacterial rather than viral infection status should be considered in the development of targeted therapies in VSCC. Prevention and control of bacterial infections are anticipated to become a valuable addition to current cancer treatment modalities [63]. Finally, several lines of evidence for similarities in the biology of ANCA-associated vasculitis provides grounds for the assumption that VSCC patients might bene t from treatments currently applied in AVV and other neutrophilic human diseases such as COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ICOS induction on T Reg has been reported in chronic infectious disease ( 43 ). This is also relevant since several of the above preferred tumours that have high levels of ICOS + T Reg are also often associated with chronic viral or bacterial infections ( 44 ). At this stage, it is not yet clear if these T Reg are pathogen-specific and are inhibiting the anti-tumour immune response as a “bystander effect”.…”
Section: Discussionmentioning
confidence: 99%